Literature Review of the Development of Sensor Technology for Monitoring Civil Engineering Infrastructure - Eric, Eric (Pt. Anagata Sembagi Education, 2025)
This study aims to examine the development of sensor technology in civil engineering infrastructure monitoring systems through a literature study approach with a qualitative descriptive method. The need for accurate, real-time, and sustainable monitoring systems is increasingly urgent as the complexity and age of public infrastructure increases. This study highlights the evolution of sensors such as strain gauges, accelerometers, and Wireless Sensor Network (WSN)-based systems that are now integrated with the Internet of Things (IoT) and edge computing. This technology enables early detection of structural damage and efficient data processing, thereby increasing the effectiveness of structural maintenance and safety. However, implementation in the field still faces challenges such as initial costs, extreme environmental conditions, and limitations of existing structures. Through content analysis of various scientific publications over the past decade, it was found that the success of the Structural Health Monitoring (SHM) system is not only determined by the quality of the sensor, but also by the data integration strategy and analytical-based decision making. This study provides academic contributions in mapping trends and challenges of sensor technology and offers practical insights for the development of adaptive and sustainable monitoring systems, especially in developing countries like Indonesia.